Profiles of honey producers, traders and consumers in the city of Barreiras – Bahia (Research, Society and Development, 2021)
This study aimed at evaluating the commercialization conditions of honey in open fairs in the city of Barreiras - BA, and assessing the profile of consumers, traders and producers. Questionnaires were applied in order to trace the profile of each segment. Regarding the buying habits, 43.6% of the consumers said they prefer to buy the product directly from the producer. The origin of the honey was the criterion justified by 46.40% when buying the product, followed by quality (28.2%).  60% of the people reported that the honey they bought did not have labels, although the majority considered the product more reliable with the presence of a label. It was possible to observe in the fairs, inadequate honey storage conditions, because besides the use of non-recommended packages, there was also direct sunlight incidence on the containers that were arranged on stands. Although most of the beekeepers and meliponiculturists informed that they have already participated in courses about Good Practices for Food Production, most of them don't put in practice the hygiene of their personal, work environment and the equipment used for honey production and bottling. The research was important to identify the profile of honey consumers, it's necessary to assimilate the wishes and needs of those who buy the product. Most of the beekeepers and meliponiculturists sell their products without label and inspection, and use reusable packages. It can be seen that the places where the products are sold, which are the fairs, do not have adequate conditions of sale, exhibition and storage.